The response of a spherical tissue-equivalent proportional counter to different heavy ions with similar velocities - Taddei, Phillip James, author; Borak, Thomas B., advisor; Durham, James, committee member; Heilbronn, Lawrence, committee member; Lee, Thomas, committee member (Colorado State University. Libraries, 2005)
A tissue-equivalent proportional counter (TEPC) has been used as an area monitor to measure absorbed dose and estimate equivalent dose during Space Transport Shuttle and International Space Station missions. This detector measures energy deposition events in simulated small volumes of tissue on the order of the size of a mammalian cell nucleus. A TEPC measures energy deposited in tissue of simulated microscopic volumes on an event-by-event basis and has a large dynamic domain of sensitivity to energy deposition events, ranging from hundreds of eV to thousands of keV. An enhanced understanding of the response of the TEPC is necessary to correctly evaluate these microdosimetric quantities. The particles of particular interest to which astronauts are exposed in space are high atomic number (atomic number, Z ≥ 2) and high energy (HZE) ions originating from galactic cosmic radiation and solar radiation. The response of a spherical tissue-equivalent proportional counter to different HZE ions having similar energy per nucleon (i.e., similar velocity) was studied using the Heavy Ion Medical Accelerator operated by the National Institute of Radiological Sciences in Chiba, Japan. Detector response was measured for 12C, 16O, 28Si and 56Fe at 376 MeV nucleon-1 (velocity relative to the speed of light, β= 0.70) and 4He and 12C at 220 MeV nucleon-1 (β= 0.59). A particle spectrometer was used to record the charge and position of each incident beam particle. This enabled reconstruction of the location of the track as it passed though the TEPC and ensured that the incident particle survived without undergoing fragmentation. Events with small energy deposition were observed for particles that passed through the wall of the TEPC but not through the sensitive volume. Events with large energy deposition were observed for particles that interacted with the anode or helical wire or grazed the inside wall of the gas cavity. Data indicated that the frequency averaged lineal energy, yf, was always less than the linear energy transfer (LET) of the incident particles. The dose averaged lineal energy, yD, was approximately equal to LET for particles with Z greater than 6 and LET greater than 10 keV μm-1, whereas yD was larger than LET for the lighter particles with lower LET. Part of this effect is due to the low energy deposition events that are often indistinguishable from noise. The small energy deposition portion of the lineal energy distribution had a similar shape for ions of similar velocity, indicating that ions of the same velocity have identical delta-ray wall effects. When using a TEPC, a lower threshold for energy deposition must be selected below which events are considered indistinguishable from noise and are eliminated from the data. Careful consideration must be made when selecting a lower threshold in the spectrum of energy deposition response of the TEPC. The choice of the lower threshold has a measurable effect on yf and yD. Although the TEPC is not an LET spectrometer, it can provide real time measurement of dose and estimation of quality for HZE particles. The energy deposition response of the TEPC can be used along with the mass of the active volume of the TEPC to measure absorbed dose. The distribution of lineal energy events may be used to estimate the average quality of the radiation and, hence, equivalent dose.
Keywords: radiology; radiation; nuclear physics; medical imaging